TUGAS, WEWENANG DAN TANGGUNG JAWAB BALAI HARTA PENINGGALAN DALAM PEMBERESAN HARTA PAILIT - Inayati, Raisa (JURNAL MEDIA HUKUM DAN PERADILAN, 2018)
Bankruptcy will essentially change the competent status of the relevant legal subject of the debtor in the management of the bankruptcy property, then in the process must follow certain terms and procedures so declared bankrupt based on a judge's decision. Due to the verdict of bankruptcy statement against the debtor will become a foothold of the next problem that is about how the creditors get their rights from the debtor bankruptcy and who will take care of the division of bankrupt debtors. Against this statement, Article 70 of Law Number 37 Year 2004 concerning Bankruptcy and Suspension of Obligation for Payment of Debts stipulates that the entitled to do belongs to The Orphans Chamber or other Curators. Closing up bankruptcy belongs to the end of the bankruptcy process. In this writing can be known about the main role in the management and ordering of bankrupt property carried out by the Curators / The Orphans Chamber.